2021
DOI: 10.1111/jcpe.13417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk/protective indicators of buccal soft tissue dehiscence around dental implants

Abstract: Aim To evaluate the prevalence of buccal peri‐implant soft tissue dehiscence (PISTD) in anterior implants and to identify the risk/protective indicators of PISTD in implants not suffering peri‐implantitis. Materials and methods 240 randomly selected patients from a university clinic database were invited to participate in the present cross‐sectional study. Those who accepted, after the evaluation of their medical and dental records, were clinically examined to assess the prevalence of buccal PISTD in non‐molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Today, it is also suggested in soft tissue augmentation. After comparing our results with previous randomised clinical trials, our data seem to be in line with the studies by Thoma et al [12] and Zeltner et al [13] regarding the buccal gain of VCMXA (0.77 ± 0.74 mm; 1.1 ± 1.4 mm) [1,12] . Unfortunately, regarding VCMXB, there are no data regarding these types of 3D evaluations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Today, it is also suggested in soft tissue augmentation. After comparing our results with previous randomised clinical trials, our data seem to be in line with the studies by Thoma et al [12] and Zeltner et al [13] regarding the buccal gain of VCMXA (0.77 ± 0.74 mm; 1.1 ± 1.4 mm) [1,12] . Unfortunately, regarding VCMXB, there are no data regarding these types of 3D evaluations.…”
Section: Discussionsupporting
confidence: 92%
“…Tooth replacement by means of dental implants is considered to be a predictable procedure in modern dentistry [1] . A key factor in predictably achieving good aesthetic and functional results in anterior restorations is to preserve or regain adequate tissue volume at the implant level [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors observed that KM is not essential to maintain periimplant health. [2][3][4][5][6][7][8] In addition, the 2017 World Workshop on Periodontal and Peri-implant Diseases and Conditions did not find any clear relationship. [9][10][11] Nevertheless, it has been reported that a wider band of KM may better preserve soft and hard tissue stability 12 being also more favorable for the long-term maintenance of dental implants.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, peri-implant diseases, particularly, peri-implantitis progresses in a nonlinear and accelerating pattern, thus, making its early diagnosis critical (7). Peri-implant diseases are, in most cases, asymptomatic and not perceived by the patients, making their diagnosis challenging (8). Thus, clinicians should continuously monitor implants in function on a regular basis.…”
Section: Introductionmentioning
confidence: 99%